Linkages to HIV confirmatory testing and antiretroviral therapy after online, supervised, HIV self‐testing among Thai men who have sex with men and transgender women. Issue 1 (20th January 2020) - Phanuphak, Nittaya; Jantarapakde, Jureeporn; Himmad, Linrada; Sungsing, Thanthip; Meksena, Ratchadaporn; Phomthong, Sangusa; Phoseeta, Petchfa; Tongmuang, Sumitr; Mingkwanrungruang, Pravit; Meekrua, Dusita; Sukthongsa, Supachai; Hongwiangchan, Somporn; et al.
Abstract: Introduction: Online, supervised, HIV self‐testing has potential to reach men who have sex with men (MSM) and transgender women (TGW) who never tested before and who had high HIV‐positive yield. We studied linkages to HIV confirmatory test and antiretroviral therapy (ART) initiation among Thai MSM and TGW who chose online and/or offline platforms for HIV testing and factors associated with unsuccessful linkages. Methods: MSM and TGW were enrolled from Bangkok Metropolitan Region and Pattaya during December 2015 to June 2017 and followed for 12 months. Participants could choose between: 1) offline HIV counselling and testing (Offline group), 2) online pre‐test counselling and offline HIV testing (Mixed group) and 3) online counselling and online, supervised, HIV self‐testing (Online group). Sociodemographic data, risk behaviour and social network use characteristics were collected by self‐administered questionnaires. Linkages to HIV confirmatory testing and/or ART initiation were collected from participants who tested reactive/positive at baseline and during study follow‐up. Modified Poisson regression models identified covariates for poor retention and unsuccessful ART initiation. Results: Of 465 MSM and 99 TGW, 200 self‐selected the Offline group, 156 the Mixed group and 208 the Online group. The Online group demonstrated highest HIV prevalence (15.0% vs. 13.0% vs. 3.4%) and high HIV incidence (5.1 vs. 8.3 vs. 3.2 per 100 person‐years), compared to the Offline and Mixed groups. Among 60 baseline HIV positive and 18 seroconversion participants, successful ART initiation in the Online group (52.8%) was lower than the Offline (84.8%) and Mixed groups (77.8%). Factors associated with unsuccessful ART initiation included choosing to be in the Online group (aRR 3.94, 95% CI 1.07 to 14.52), <17 years old at first sex (aRR 3.02, 95% CI 1.15 to 7.92), amphetamine‐type stimulants use in the past six months (aRR 3.6, 95% CI 1.22 to 10.64) and no/single sex partner (aRR 3.84, 95%CI 1.36 to 10.83) in the past six months. Conclusions: Online, supervised, HIV self‐testing allowed more MSM and TGW to know their HIV status. However, linkages to confirmatory test and ART initiation once tested HIV‐reactive are key challenges. Alternative options to bring HIV test confirmation, prevention and ART services to these individuals after HIV self‐testing are needed.